calc. practice test2 - Create assignment, 59515, Practice...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
Create assignment, 59515, Practice 2, Oct 21 at 12:19 am 1 This print-out should have 30 questions. Multiple-choice questions may continue on the next column or page – fnd all choices beFore answering. The due time is Central time. CalC3f01c 49:04, calculus3, multiple choice, > 1 min, wording-variable. 001 ±ind the derivative oF f ( x ) = 3 x sin 4 x + 3 4 cos 4 x. 1. f 0 ( x ) = 12 x cos 4 x 2. f 0 ( x ) = 12 x cos 4 x + 6 sin 4 x 3. f 0 ( x ) = - 12 x cos 4 x 4. f 0 ( x ) = 12 x cos 4 x - 6 sin 4 x 5. f 0 ( x ) = 12 cos 4 x CalC3f01d 49:04, calculus3, multiple choice, > 1 min, wording-variable. 002 Determine f 0 ( x ) when f ( x ) = 2 sin 3 x - 3 cos 2 x. 1. f 0 ( x ) = 6(cos 3 x + sin 2 x ) 2. f 0 ( x ) = - 6(sin 2 x + cos 3 x ) 3. f 0 ( x ) = 2 cos 3 x - 3 sin 2 x 4. f 0 ( x ) = 2 cos 3 x + 3 cos 2 x 5. f 0 ( x ) = - (3 sin 2 x + 2 cos 3 x ) 6. f 0 ( x ) = 6(cos 3 x - sin 2 x ) CalC3f02a 49:04, calculus3, multiple choice, > 1 min, wording-variable. 003 ±ind f 0 ( x ) when f ( x ) = x + 1 x - 1 · 2 . 1. f 0 ( x ) = - 4( x + 1) ( x - 1) 3 2. f 0 ( x ) = 6( x - 2) ( x + 1) 3 3. f 0 ( x ) = - 6( x + 2) ( x - 1) 3 4. f 0 ( x ) = - 4( x + 2) ( x - 1) 3 5. f 0 ( x ) = 6( x - 1) ( x + 1) 3 6. f 0 ( x ) = 4( x - 1) ( x + 1) 3 CalC3f06a 49:04, calculus3, multiple choice, < 1 min, wording-variable. 004 ±ind the derivative oF y when y = 2 sin x - 6 x cos x. 1. y 0 = 3 sin x - 2 cos x x · 2. y 0 = sin x + 2 cos x x · 3. y 0 = 3 sin x - 4 cos x x · 4. y 0 = sin x + 4 sin x x · 5. y 0 = 3 cos x - 4 sin x x ·
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Create assignment, 59515, Practice 2, Oct 21 at 12:19 am 2 6. y 0 = cos x + 2 sin x x · CalC3f25a 49:04, calculus3, multiple choice, < 1 min, wording-variable. 005 Find the derivative of f when f ( x ) = ( x 2 + 4) 1 / 4 ( x + 6) 1 / 2 . 1. f 0 ( x ) = 3 x - 2 2( x 2 + 4) 3 / 4 ( x + 6) 3 / 2 2. f 0 ( x ) = 3 x - 2 ( x 2 + 4) 3 / 4 ( x + 6) 3 / 2 3. f 0 ( x ) = 3 x + 2 2( x 2 + 4) 3 / 4 ( x + 6) 3 / 2 4. f 0 ( x ) = 3 x + 2 ( x 2 + 4) 1 / 4 ( x + 6) 3 / 2 5. f 0 ( x ) = 3 x + 2 2( x 2 + 4) 3 / 4 ( x + 6) 1 / 2 6. f 0 ( x ) = 3 x - 2 ( x 2 + 4) 1 / 4 ( x + 6) 1 / 2 CalC3g05c 49:05, calculus3, multiple choice, > 1 min, wording-variable. 006
Background image of page 2
Image of page 3
This is the end of the preview. Sign up to access the rest of the document.

Page1 / 9

calc. practice test2 - Create assignment, 59515, Practice...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online